CIDADANIA NA ESCOLA - HEUSER, ESTER E.; GATTO, JOAQUIM H.; RAMOS, LIZÉLIA T.; CABRAL, TACIANE; KOSCHECK, SUELI; HAMMARSTROM, FERNANDA M.; ZANATTA4, LUCIANE; KREIN, ROMEU; RIBEIRO, CELSO (Salão do Conhecimento, 2013)
Resumo